A History of the Middle East 1.01 - Flynn, Robert J. (Open textbook library., 2021)
History of the Middle East is a survey of Middle Eastern History from the time of Muhammad in the seventh century until the eve of the War on Terror in 2001. It is designed to meet the requirements of a single-term introductory course and is aimed at students who have no more than a casual understanding of the history, cultures, and societies of the region. It offers a relatively concise narrative of the region’s historical development that seeks to avoid oversimplification on the one hand and overcomplexity on the other.